Impact Of Antioxidants Activity On Enzymes Of Seminal Plasma In Association With Mental Stress Subjects - VIJAY R. PANDHARE; PRAMOD S. KAMBLE; PRAKASH D. ZENDE (International Journal of Pharma and Bio Sciences, 2012)
In the present study we investigated the impact of mental stress in medical students due to final examination on free radical activity and three important antioxidant enzymes of seminal plasma, Superoxide Dismutase(SOD), Glutathione Peroxidase(GSH) and Catalase in normal medical students. For carrying out morphological and biochemical analysis, semen samples were collected thrice from 50 healthy male volunteers, who were third semester students of a medical college, just before and after stress period 12.00±0.50 week final examination and 12.00±0.50 week gap after final examination. Venous blood samples were also withdrawn and serum was separated for assessment of cortisol levels. Psychological stress of participants and non-stress subjects were assessed on the basis of questionnaire and elevated serum cortisol level. The results demonstrated spermatozoa concentrations, motility index and percentage of rapid progressive motility decreased under stress. Moreover, serum cortisol and seminal plasma Lipid Peroxide (LPO) levels were found elevated along with decreased seminal plasma GSH and reduced SOD.